Attachment Disorder behavior in early and middle childhood: associations with children's self-concept and observed signs of negative internal working models. Issue 2 (4th March 2019) - Zimmermann, Peter; Iwanski, Alexandra
ABSTRACT: Most research on attachment in childhood is based on observation. In contrast, research on reactive attachment disorder (RAD) is mainly based on caregiver reports. Moreover, little is known about self-concept or internal working models (IWMs) of self and others in children with RAD. The present study examined whether caregiver reports and the frequency of observed signs of RAD reveal differences between children at risk for developing RAD symptoms and healthy controls in middle childhood. In addition, children's self-concept, observable signs of negative IWMs, and mental health were assessed. Results revealed that the RAD risk group showed increased reported and observed signs of RAD, a more negative self-concept, and more signs of negative IWMs compared to healthy controls. Signs of RAD in middle childhood were expressed trans-relational to both caregivers and strangers. Moreover, RAD symptoms were associated with negative self-concept, observed signs of negative IWMs, and poor mental health.